ANCAMAN STRATEGI HYBRID WARFARE RUSIA: SEBUAH PERSEPSI DAN MANIFESTASI KEBIJAKAN ESTONIA - Dyah Lupita Sari (Review of International Relations, 2019)
In recent years, Russia has developed a hybrid warfare strategy as a tactic to carry out war operations to achieve their national interests. Estonia is considered the most vulnerable country in the face of the threat of a Russian hybrid warfare strategy. In this case, Estonia has historical, geopolitical and political value for Russia. Estonia has received signs of the Russian threat manifested through their aggressive actions in Estonia with hybrid projections that have been projected in a real way. Thus, the Russian hybrid warfare strategy can influence the perception of the Estonian threat which was finally responded through a policy to stem the threat of hybrid itself. Underlying the analysis of the Threat Perception theory proposed by Raymond Cohen, this paper will explain how the Estonian threat is perceived by the Russian hybrid warfare strategy by looking at the threatening cue and responses to the  threats. This paper has the argument that the hybrid warfare strategy is a threat to Estonia. The historical factor of Russian-Estonian relations and past experience of threats is a sign of a threat that influences the perception of Estonian threats. Estimation of the threat was then manifested by Estonia in the form of anticipatory actions through increased cooperation with NATO, an increase in Estonia's military capabilities, and other non-military approaches in counter Russian warfare hybrid strategy. Keywords: Hybrid Warfare, Russia, Estonia, threat perception, threatening cue, asymmetric threat, cyber security, disinformation, NATO